Water storage: a contribution to climate change adaptation in Africa - Eguavoen, I.; McCartney, Matthew P. (2013)
Water storage can help to safeguard livelihoods and reduce rural poverty. However, ill-conceived water storage will fail to deliver intended benefits and, in some cases, may worsen the negative impacts of climate change. More systematic planning is required to ensure suitable storage systems that support development targets, as an international research project demonstrates.